CINTA DAN RUPIAH TERHADAP KUALITAS PENDIDIKAN ISLAM DAN SOSIAL MASYARAKAT BUGIS DI DESA DALIL KEC BAKAM DAN SUNGAI LIAT - DG Tujuh, syarifah21 HR (Tarbawy : Jurnal Pendidikan Islam, 2023)
Love is one of the basic things that exists to perfect a couple's marriage as they navigate  the  household.  In  Bugis  society  apart  from  love,  rupiah  is  also  an important  thing  that  must  exist  before  stepping  into  marriage.  Usually  this rupiah  is  termed  Panaik  Money.  For  the  Bugis  community,  there  is  no banknote/rupiah, so there is no marriage. Even when two lovebirds like each other and even fail to get married because there is no agreement regarding the rupiah that the man must hand over to the woman in a fantastic amount, then something called silariang or elopement appears. In this study, researchers will see how the position of the rupiah is if it has been linked to Islamic education and  social  education.  Giving  Panaik  money  in  traditional  Bugis  Makassar marriages  is  not  regulated  in  Islamic  law.  Islamic  law  only  requires  the prospective groom to pay a dowry to the prospective bride and even then it is recommended for the woman not to ask for excessive dowry.The  amount  of  Panaik  money  that  must  be  submitted  depends  on  the  social status, education, physical condition, and occupation of the prospective bride. The higher the social status of his future wife, the higher the amount that must be given. Social education is related to the values contained in giving rupiah, which   are   sometimes   fantastic   amounts,   especially   the   transmigrant community in the Bangka Belitung Islands. In this study, the Bugis community in Kec.  Bakam  and  Clay  River.  Research  data  was  collected  using  interview techniques and documentary observation.